Seroprevalence and Risk Factors for Epstein-Barr Virus Infection in Adults - Jale ALTINTAŞ; Serpil EROL; Derya ÖZTÜRK ENGİN; Seyfi ÖZYÜREK; Seniha ŞENBAYRAK; Asuman İNAN; Zeynel Abidin DEMİR (Mediterranean Journal of Infection, Microbes and Antimicrobials)
Introduction: Epstein-Barr virus (EBV), also known as human herpesvirus 4, is the causative agent of infectious mononucleosis. Infection with EBV is associated with multiple malignancies. The aim of this study was to determine the seroprevalence and risk factors for seropositivity. Materials and Methods: This study was conducted in Haydarpaşa Numune Training and Research Hospital in İstanbul between August 2012 and October 2012. Epstein-Barr virus viral capsid antigen IgG antibody was measured using ELISA in 500 cases. Age, gender, occupation, education level, family income, the area and type of residence, and chronic illness of the participants were also evaluated. Differences between risk groups were statistically analyzed. Results: The mean age of the 500 study participants was 47.7±19.1 (15-87) years and 289 (57.8%) were male. Mean EBV seropositivity was 96.4%, and 91% of the cases became seropositive for EBV by 15 years of age. No significant associations with age, gender, occupation, education level, family income, area and type of residence, and chronic illness were detected. Conclusion: Epstein-Barr virus seropositivity rates were very high and about 91% of the cases become seropositive for EBV by 15 years of age. There was no significant relationship between risk factors and seroprevalence of EBV.